2019
DOI: 10.1016/j.ajo.2019.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Correlations Between Diabetes and Glaucoma: An Analysis of Continuous and Dichotomous Phenotypes

Abstract: A genetic correlation is the proportion of phenotypic variance between traits that is shared on a genetic basis. Here we explore genetic correlations between diabetes-and glaucoma-related traits. Design: Cross-sectional study. Methods: We assembled genome-wide association study summary statistics from Europeanderived participants regarding diabetes-related traits like fasting blood sugar (FBS) and type 2 diabetes (T2D) and glaucoma-related traits (intraocular pressure (IOP), central corneal thickness (CCT), co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 66 publications
3
8
0
Order By: Relevance
“…Eight of the POAG loci did not appear to have a clear effect on IOP or VCDR, although a small effect on glaucoma via a small change in IOP or VCDR could not be ruled out. The overall correlation of effect sizes between all POAG risk loci and IOP was 0.53, and between POAG and VCDR was 0.31, in line with previously published genetic correlation estimates 25 . To better visualize clustering of the POAG SNPs based on their effect on IOP/VCDR, we created a heatmap by clustering SNPs based on Pearson correlation between effect estimates of SNPs on POAG, IOP, and VCDR (Supplementary Fig.…”
Section: Resultssupporting
confidence: 89%
“…Eight of the POAG loci did not appear to have a clear effect on IOP or VCDR, although a small effect on glaucoma via a small change in IOP or VCDR could not be ruled out. The overall correlation of effect sizes between all POAG risk loci and IOP was 0.53, and between POAG and VCDR was 0.31, in line with previously published genetic correlation estimates 25 . To better visualize clustering of the POAG SNPs based on their effect on IOP/VCDR, we created a heatmap by clustering SNPs based on Pearson correlation between effect estimates of SNPs on POAG, IOP, and VCDR (Supplementary Fig.…”
Section: Resultssupporting
confidence: 89%
“… 20 , 21 To what extent an IOP PRS captures a family history of glaucoma is unknown. The variance of corneal-compensated IOP in the UK Biobank explained by GWAS SNPs 46 and the IOP PRS is approximately 15% and 4%, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, the link between diabetes and POAG-related traits, including IOP, remains controversial in recent findings from genome-wide association studies [57][58][59] . Although Shiga et al found a significant positive correlation between diabetes and POAG in a Japanese population 57 , another Japanese genetic study 58 and a study in Europeans 59 found no such association.…”
Section: Discussionmentioning
confidence: 99%